Incidence of Sacroiliitis among Patients Presenting with Chronic Low Back Pain to a Tertiary Care Spine Center - Apoorv Kumar; Bhavana Girishekar; Vijay KR Rao; Thomas J Kishen (Journal of Orthopedics and Joint Surgery)
Inflammatory spondyloarthropathy (SpA) is an underdiagnosed cause of chronic low back pain leading to prolonged suffering and numerous visits to hospitals. The aim of this study was to ascertain the prevalence of sacroiliitis, which is an early indicator of inflammatory SpA, among patients who present with chronic low back pain. Materials and methods: A total of 200 consecutive lumbosacral (LS) spine MRI scans performed at Manipal Hospitals, Bengaluru, Karnataka, India, were analyzed by two radiologists and a spine fellow. The demographic data of the patients and the presence of sacroiliitis and other abnormalities on the scans were noted. Results: Among the 200 patients included in the study, 119 were male, and 81 were female, with a mean age of 35.07 years. A total of 31 (15.5%) patients were diagnosed to have sacroiliitis, which included 14 males (11.76%) and 17 females (20.99%). Conclusion: The study showed that 15.5% of patients who presented with low back pain had sacroiliitis, which is more than previously reported. Thus, it is important to carefully assess the sacroiliac joints of low backache patients both clinically and radiologically so that the diagnosis is not missed and appropriate treatment can be given. Clinical significance: This article stresses the fact that the clinician must always look into the sacroiliac joints, both clinically and radiologically, of any patient presenting with complaints of low backache in the outpatient department.